Kontribusi Atraksi Wisata Arung Jeram Terhadap Masyarakat Lokal Di Desa Pekraman Kedewatan Kecamatan Ubud, Kabupaten Gianyar - I Wayan Dedy Karnawan; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
The existence of a tourist attraction required improving the welfare of the surrounding community. This study aims to find out how many contributions of rafting tourist attraction in society Kedewatan village, in order to contribute positively to the welfare of local communities. Therefore, this research is expected to provide benefits to related parties. This researchused of primary data and secondary data sources, while the type of data used quantitative and qualitative data. Data were collected through observation, interview and literature study. Determination of informants in this research usedpurposive sampling technique. The data analysis used is qualitative data analysis techniques and restricted by contribution concept, the concept of community participation, and the concept of community-based tourism. The results obtained are the company's contribution to Kedewatan society been running smoothly, which contributes to the Kedewatan village in the form of donations which pay each month, contributing directly to the public in the form of add job vacanciesfor local people, contributing indirectly to the local communities that helping local community businesses. To optimizie job vacanciesfor local communities,it is necessary to co-operation between companies and Kedewatan communities in recruitment labor. Keywords: Contributions, rafting, Kedewatan village community